1997
DOI: 10.1016/s0735-1097(97)00147-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electron Beam Computed Tomography With Intracoronary Ultrasound and Coronary Angiography for Detection of Coronary Atherosclerosis

Abstract: This in vivo correlation between ICUS and EBCT demonstrates that EBCT is a noninvasive method that helps to visualize the atherosclerotic process by localization and quantification of coronary artery calcifications. EBCT detects calcified plaques with high accuracy. Plaques without ultrasound signs of calcifications can be detected by EBCT but with lower sensitivity but equivalent specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0
13

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(139 citation statements)
references
References 33 publications
2
124
0
13
Order By: Relevance
“…In addition, calcification is a measure of stabilized plaque but may not always account for the noncalcified plaque burden (ie, the type that is vulnerable for rupture). Nonetheless, studies have found that CAC can reliably predict future adverse cardiovascular events, correlates well with cardiac computed tomography angiography findings of significant angiographic stenosis, 45 is cost-effective, 46 and provides an additive benefit to existing cardiovascular risk assessment tools. 47 The beneficial role of CAC in cardiovascular risk assessment of type 2 diabetes has been well established.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, calcification is a measure of stabilized plaque but may not always account for the noncalcified plaque burden (ie, the type that is vulnerable for rupture). Nonetheless, studies have found that CAC can reliably predict future adverse cardiovascular events, correlates well with cardiac computed tomography angiography findings of significant angiographic stenosis, 45 is cost-effective, 46 and provides an additive benefit to existing cardiovascular risk assessment tools. 47 The beneficial role of CAC in cardiovascular risk assessment of type 2 diabetes has been well established.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is now widely accepted that the presence of calcium in coronary arteries is pathognomonic of atherosclerosis, 3 and a close correlation between the atherosclerotic plaque burden and the extent of CAC has been confirmed both by histopathology and intravascular ultrasound, with the total CAC score representing an anatomic measure of overall coronary plaque burden. 4,5 In this context, there has been an exponential increase in interest in cardiac computed tomography as applications expanded from the identification of CAC to noninvasive coronary angiography, through obtaining cross-sectional images of the heart in subsecond scanning times and accurately detecting and quantifying even small areas of CAC. 6 Among inflammatory cells, leukocyte recruitment and the expression of proinflammatory cytokines related to leukocyte activation have been shown to characterize all steps of atherothrombosis.…”
mentioning
confidence: 99%
“…A similar study by Rumberger et al 23 , correlating coronary artery calcium quantification on ultrafast tomography in hearts at autopsy and its histopathologic quantification, confirmed these data. Angiographic and coronary artery ultrasound studies have also shown that coronary artery calcification correlates with the load of the atherosclerotic plaque [8][9][10] , and the latter, in turn, correlates with the risk for coronary events [5][6] . Several studies in asymptomatic or symptomatic individuals on coronary artery disease have shown a correlation between coronary artery calcification and obstruction of the lumen of the vessel 9,18,24 .…”
Section: Discussionmentioning
confidence: 99%
“…1), detected on ultrafast computed tomography or electron beam computed tomography, correlates with the load of the atherosclerotic plaque in histological, angiographic, and intravascular ultrasound studies [7][8][9][10] . Ultrafast computed tomography is a noninvasive and very sensitive method to detect calcification in coronary arteries 7 .…”
Section: Distribution Of Coronary Artery Calcium Scores Determined Bymentioning
confidence: 99%